The Effect of Sombere Education on Stress Levels in Primigravida Pregnant Women - Sudirman, Jumrah; Syafar, Muhammad; Jusuf, Elizabet Catherine; K, Rahayu Eryanti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Mental health problems during pregnancy are major public health issues that require immediate attention. Anxiety and stress can have an impact on pregnancy and childbirth. This study examines the impact of Sombere education on the stress levels of pregnant women. A quasi-experimental design with a pre-test and post-test design and a control group was employed in this study. This study's sample consisted of 80 primigravida pregnant women who met the sample criteria. Purposive sampling was utilized in this study. The chi-square test and the Wilcoxon rank test were implemented to analyze the data. The findings of this study revealed that there was a difference in stress in the intervention group after treatment (p=0.000<0.005), as well as a difference in stress in the control group during the post-test (p=0.001<0.005). Sombere education has an effect on stress levels in primigravida pregnant women (p=0.016<0.005). The requirement Midwives provide education on maternal mental health, particularly the stress of pregnancy. In addition, midwives must conduct stress assessments or collaborate with psychologists to ensure pregnant women's mental health.